Social Gatherings and Live Music: A Qualitative Study of Bajawa Tebet Coffee Consumer Behavior - Tarigan, Ireine Christy (International Journal of Science and Society, 2025)
Consumer behavior is an aspect related to individuals and organizations and how they choose and use products, with environmental factors making someone able to change their decision to choose a product or service. This study was conducted to find out how social gatherings and live music occur and a qualitative study of consumer behavior at Kopi Tebet Bajawa. This study uses the theory of reasoned action. The method used in this study is a qualitative method. Data collection was carried out through direct interviews and online interviews. The results of this study are that with the live music provided by Kopi Tebet Bajawa, of course there will be changes. The first is the social gathering experienced by consumers, namely for consumers who love music, it will be easier to mingle and chat about the songs performed by the live music team, then the second is a change in consumer behavior, namely a change in emotions with live music, people who used to be sad and depressed with their personal lives can automatically express their emotions at Kopi Bajawa Tebet.